SERVING TWO MASTERS: SKOPOSTHEORIE AND ETHNOLINGUISTIC TRANSLATION ORIENTATION - Harris Hermasnyah Setiajid (Universitas Bandar Lampung, 2023)
The skopostheorie and ethnolinguistic translation orientation are two important concepts in the field of translation studies. The skopostheorie, first introduced by Hans J. Vermeer, focuses on the functional aspect of translation, specifically on the communicative purpose or